Model construction and implementation of Ordos Energy Super Basin, NW China - Ailin JIA; Fangxuan CHEN; Naichao FENG; Dewei MENG; Shuai ZHENG (Petroleum Exploration and Development, 2024)
Taking the Ordos Basin as an example, this paper proposed that the construction of an energy super basin should follow the principle of “more energy, less carbon, and better energy structure”. The modeling workflow of energy super basin was built. Based on the resources/reserves, development status and infrastructures of the Ordos Basin, the development potential of the basin was evaluated, the uncertainties in the construction of energy super basin were analyzed, and the future vision and realization path of the Ordos Energy Super Basin were recommended. This study demonstrates that the Ordos Basin has the advantages of abundant energy sources, perfect infrastructures, well-matched carbon source and sink, small population density, and proximity to the energy consumption areas. These characteristics ensure that the Ordos Basin is a good candidate of the energy super basin. It is expected that the energy supply of the Ordos Basin in 2050 will reach 23×108 t of standard coal, and the proportion of fossil fuels in energy supply will decrease to 41%. The carbon emissions will decrease by 20×108 t compared to the emissions in 2023. The future construction of the basin should focus on the generation and storage of renewable energy, and technological breakthroughs for the carbon capture, utilization and storage.